The complementary and alternative medicine (CAM) product information brochure: how is generic structure used to persuade potential users? - Goh, Ching Fen; Chan, Mei Yuit; Mohd Ali, Afida; Md Rashid, Sabariah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The presence and influence of complementary and alternative therapies have been increasingly felt in recent years. One reason for this is the active promotion of its services and products through various media channels. The current study focused on information brochures that are placed on pharmacy counters and shelves, and examined how they function as persuasive texts in promoting products and persuading potential users to buy them. The study utilised genre analysis as a method for examining how language and information in texts are systematically selected and structured to perform particular actions and achieve particular communicative purposes. Genre hybridisation as a theoretical concept is drawn on to explain the inter-generic realisation of forms of discourse. One hundred brochures providing information on complementary and alternative health products produced by pharmaceutical companies were collected from pharmacies in Malaysia and analysed for their communicative content in terms of rhetorical moves used to promote the products. This paper describes the generic structure of the print content in the brochures and discusses how it functions to present a favourable view of complementary and alternative health products to the reader. The results show that across all the brochures, regardless of the type of product, a uniform set of moves that is comparable to the sales promotional genre is identified. The findings also reveal that such information brochures on pharmacy counters are in fact persuasive promotional literature. As these brochures are ubiquitous in pharmacies and drugstores in most countries, they are an important force in influencing consumer and patient knowledge, and beliefs about complementary and alternative medicine.